2022
DOI: 10.3389/fimmu.2022.950076
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of potential pathogenesis and risk genes of immunoinflammation-promoted renal injury in severe COVID-19

Abstract: Renal injury secondary to COVID-19 is an important factor for the poor prognosis of COVID-19 patients. The pathogenesis of renal injury caused by aberrant immune inflammatory of COVID-19 remains unclear. In this study, a total of 166 samples from 4 peripheral blood transcriptomic datasets of COVID-19 patients were integrated. By using the weighted gene co-expression network (WGCNA) algorithm, we identified key genes for mild, moderate, and severe COVID-19. Subsequently, taking these genes as input genes, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…LYN is Tyrosine-protein kinase Lyn, which plays an important role in the developmental maturation of B cells, the positive and negative regulation of inflammatory responses and the co-catalysis of T cells ( Brian and Freedman, 2021 ). LYN has been less studied in relation to COVID-19, but recent related studies have shown that LYN has an important relationship with severe COVID-19 ( Chen et al, 2022 ). HCK is the tyrosine protein kinase HCK, which plays an important role in hemopoiesis, regulation of the innate immune response and release of inflammatory molecules ( Podar et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LYN is Tyrosine-protein kinase Lyn, which plays an important role in the developmental maturation of B cells, the positive and negative regulation of inflammatory responses and the co-catalysis of T cells ( Brian and Freedman, 2021 ). LYN has been less studied in relation to COVID-19, but recent related studies have shown that LYN has an important relationship with severe COVID-19 ( Chen et al, 2022 ). HCK is the tyrosine protein kinase HCK, which plays an important role in hemopoiesis, regulation of the innate immune response and release of inflammatory molecules ( Podar et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…HCK is the tyrosine protein kinase HCK, which plays an important role in hemopoiesis, regulation of the innate immune response and release of inflammatory molecules ( Podar et al, 2004 ). HCK has been identified as an important pharmacological target for improving lung function in patients with COVID-19 and has been significantly associated with COVID-19 in studies comparing healthy individuals with patients with severe COVID-19 ( Chen et al, 2022 , Chakraborty et al, 2021 ). In short, the selected hub targets elucidate the pharmacological mechanisms of action of cepharanthine for the treatment of COVID-19 at the level of antiviral, organismal metabolism, anticoagulation, and regulation of inflammatory and immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that SARS-CoV-2 infection can cause a myriad of complications because there are common genes between COVID-19 and these complications. 23–26 Therefore, this study aimed to explore the possible genetic relationship between COVID-19 and PE through bioinformatics to reveal the underlying pathogenesis of susceptibility to PE events in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative bioinformatics approaches have been employed to determine the association between gastrointestinal and cardiovascular diseases and COVID-19 infection. 7 In this regard, transcriptome analyses of non-coding and coding elements should be able to identify risk factors at the molecular level that can be used to identify individuals that are likely to develop severe COVID-19, thus allowing for the development of early intervention strategies and customized therapeutic options. 8 Gene expression profiling has been conducted in individuals infected with SARS-CoV-2 to characterize the association of certain gene expression patterns with the disease.…”
Section: Introductionmentioning
confidence: 99%